Teachers’ Language Assessment Literacy: Indonesian Secondary EFL Teachers’ Knowledge, Perspective, and Classroom Practice - Damayanti, Fury Yulia; Setyaningsih, Endang; Sumardi, Sumardi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
The primary objective of this study was to investigate secondary school EFL teachers' understanding, perspectives, and classroom practices regarding language assessment literacy. This research was conducted in three different backgrounds of schools. This study employed case study research and the theoritical framework of the Teachers Assessment Literacy Questionnaire (TALQ) proposed by Plake et al. The data was obtained by the questionnaire, interviews, and classroom observation, then analyzed using thematic analysis. The result showed that the teachers already had excellent knowledge and positive perspectives regarding assessment literacy. Their knowledge, perspective, and classroom practice involved a) the relevance between assessment method and instructional objectives, b) the development of assessment and management of learning outcomes, c) the benefits of assessment, d) the form of assessments, e) the ranking of assessments results f) unethical action in conducting assessment. This study might contribute to the teachers' carrying out assessments following standards, and educational institutions should be aware of the teachers' competency to increase teachers' competence and enthusiasm in carrying out better assessments.